Mortgage Lending in the Palestinian Territories : Fundamentals for Judges and Lawyers - Palestinian Judicial Training Institute; World Bank; USAID (World Bank, Washington, DC, 2013)
This document describes the training course for lawyers and judges in the Palestinian Territories, which was designed as an introduction to residential mortgage lending, and the use of mortgage collateral. These materials begin with a technical description of mortgage lending and mortgage collateral, the purposes and content of mortgage law, and the general conditions for development and expansion of residential mortgage lending activity. This is followed by a discussion of mortgage lending from the perspective of the financial institutions that originate most loans, including the process of making the loan and the economics of mortgage lending. The sections on economics of mortgage lending include the costs to the creditor, the risks faced by residential mortgage creditors, how creditors determine interest rates and other loan terms, and the effect of loan terms on the ability of citizens to borrow. The discussion of the economics of mortgage lending also focuses on recent research showing how laws affecting creditors' rights and court enforcement of creditors' rights may affect the amount and terms of mortgage lending in a country. The document includes a review and discussion of the current mortgage law in the West Bank and Gaza, focusing on formal requirements for creation of the mortgage and the procedures for enforcing mortgage liens against real property. A glossary of terms common to mortgage lending is included at the end of these materials for convenience.